A NEW FACE OF CARIES: INNOVATIONS AND APPROACHES IN DIAGNOSTICS - Sunnatov Davron Xusniddin o’g’li; Xamidov Murodjon Alisher o’g’li; Khatamov Ulug'bek Altibayevich (Scholar Express Journals, 2025)
This article discusses the urgent aspects of early detection of caries disease and diagnostics through modern technologies, analyzing advanced diagnostic methods used to identify various forms of caries disease and assessing their effectiveness. The study involved an analysis of scientific literature, clinical observations, and the examination of modern technological tools, including DIAGNOdent, radiovisiography, and optical imaging systems[12]. According to the research findings, advanced diagnostic methods play a crucial role in the early detection of caries, accurate diagnosis, and the establishment of treatment strategies. In conclusion, the new "face" of caries—its development in a latent form without clinical signs—necessitates a fundamental shift in dental diagnostic approaches
Keywords: caries; early diagnosis; DIAGNOdent